10.1371/journal.pmed.0020297 (CrossRef Listing of Deleted DOIs, 2000)
Tropical Storm Daniel struck northeastern Libya on 10 September 2023, leading to the collapse of two dams and catastrophic floods. The disaster resulted in massive casualties and infrastructure damage, and led to infectious disease outbreaks. This study aimed to summarize the incidence and distribution of infectious diseases reported after the flood, describe temporal and geographical trends, and public health implications. We retrospectively reviewed 90 daily epidemiological reports produced by the National Routine Surveillance System (NRSS) between 14 September and 24 December 2023. From each report, we extracted the number of new cases of infectious diseases recorded by district and age group. Population-standardized incidence rates were computed per 100,000 population at the district level to observe temporal trends across the ecological unit for all infectious diseases according to Libyan infectious disease surveillance guideline, moreover weekly moving averages, and geographic distribution maps were drawn. A total of 27,368 infectious disease cases representing 15 different diseases were reported. Respiratory infections (14,031 cases; 701.67/100,000 population) and diarrhea (12,082 cases; 604.21/100,000 population) were the most common. The surveillance also identified skin-related conditions (chickenpox and rashes), vaccine-preventable diseases (measles and rubella), and vector-borne illnesses (leishmaniasis and malaria). Diarrheal cases peaked around 42 days post-flood, then declined following a local educational intervention promoting safe water practices. Geographically, Benghazi had the highest respiratory infection count, while Albayda reported the most diarrheal cases. Notably, high-threat pathogens such as cholera were not detected, and the number of malaria and measles cases remained minimal. The peak of diarrheal diseases occurred six weeks post-flood, then declined following educational intervention. Results suggest that disaster preparedness, safe water supply, and enhanced surveillance capacity are essential. These results highlight the consequences of limited resources and weak infrastructure preparedness on the spread of infectious diseases.